ANALISIS COVERAGE AREA OPENBTS MENGGUNAKAN USRP N210 - Putra, Muhammad Daffa Ramadhan; Kusmaryanto, Sigit; Mustofa, Ali (Jurnal Mahasiswa TEUB, 2024)
The development of cellular communication technology has transformed the way we interact and access information in ourdaily lives. Cellular networks based on GSM (Global System for Mobile Communications) remain one of the dominant technologies in the telecommunications world. However, in some cases, challenges related to signal coverage still persist, especially in remote areas or those affected by disasters. This research aims to address these issues. Researchers have built a GSM network using the Open BTS system, an open-source software project that has revolutionized the way cellular networks can be implemented flexibly and affordably. The construction of Open BTS is much more affordable than building conventional BTS, and in times of disaster, communication is crucial and must be quickly available. By using Open BTS and USRP N210 hardware, there is potential toovercome signal coverage issues in GSM networks. Based on the experimental data conducted, the placement distance of Open BTS and the height placement of Open BTS antennas need to be considered. This is because the farther the distance between Open BTS and the users' mobile phones, the higher the delay experienced during call and SMS services. In this study, the furthest distance of 20 meters and a height of 3 meters resulted in an average call delay of 14.27 seconds and an average SMS delay of 34.84 seconds. Conversely, the closest distance of 5 meters and an Open BTS antenna height of 0 meters compared to the user's phone resulted in an average call delay of 9.15 seconds and an average SMS delay of 11.65 seconds. The distance and height variations of Open BTS also affect the signal strength received by the users' phones. Keywords: Mobile Communication, OpenBTS System, GSM Network, Signal Coverage, Antenna Placement Effects